Civic and liberal Presbyterian pedagogy in the district of Zitacuaro, 1894 - 1905 (Tzintzun, Revista de Estudios Históricos, 2016)
In 1901 during the sessions of the Liberal Congress in San Luis Potosi, Presbyteriandelegates from the District of Zit4cuaro including the sisters Aurora, Guadalupeand Elvira Colin, Benita Reyes Anaya, and Presbyterian supporter José TrinidadPerez, attended as delegates of the Liberal Club Josefa Ortiz de Dominguez andFrancisca Carrillo and the Club Vigilant Democracy. The first consists of womenand the second of men. The purpose of going to San Luis was with the intention of“putting a grain of sand” in the building and respect for the democratic system un-der two premises: First, respect for the Mexican Constitution of 1857 and second,walking in strict accordance with the Laws of Reformation. On their return fromSan Luis Potosi, the Presbyterian delegates from Zitacuaro implemented some ofthe resolutions of the Congress, including instilling in the population a “civic ped-agogy” through Presbyterians and liberal schools founded. In response, this paperaddresses the civic and liberal pedagogy conducted by the Presbyterian Church ofZitécuaro during the years of 1894-1904.
Keywords: Civic Pedagogy; The liberal school; Presbyterianism; liberalism; Catholicism; Catholic education